The Suppression of Taboo Word Spoonerisms Is Associated With Altered Medial Frontal Negativity: An ERP Study - Wagner-Altendorf, Tobias A.; Gottschlich, Carolin; Robert, Carina; Cirkel, Anna; Heldmann, Marcus; Münte, Thomas F. (Frontiers in Human Neuroscience, 2020)
The constant internal monitoring of speech is a crucial feature to ensure the fairly error-free process of speech production. It has been argued that internal speech monitoring takes place through detection of conflict between different response options or “speech plans”. Speech errors are thought to occur because two (or more) competing speech plans become activated, and the speaker is unable to inhibit the erroneous plan(s) prior to vocalization. A prime example for a speech plan that has to be suppressed is the involuntary utterance of a taboo word. The present study seeks to examine the suppression of involuntary taboo word utterances. We used the “Spoonerisms of Laboratory Induced Predisposition” (SLIP) paradigm to elicit two competing speech plans, one being correct and one embodying either a taboo word or a non-taboo word spoonerism. Behavioral data showed that inadequate speech plans generally were effectively suppressed, although more effectively in the taboo word spoonerism condition. Event-related potential (ERP) analysis revealed a broad medial frontal negativity (MFN) after the target word pair presentation, interpreted as reflecting conflict detection and resolution to suppress the inadequate speech plan. The MFN was found to be more pronounced in the taboo word spoonerism compared to the neutral word spoonerism condition, indicative of a higher level of conflict when subjects suppressed the involuntary utterance of taboo words.